The Effect of Fibroblast Growth Factors in Grafted Fascia into the Vocal Fold of Rabbits - Carvalho, Eduardo G. B.; Machado-Júnior, Almiro J.; Pauna, Henrique F.; Nicola, Ester M.D.; Altemani, Albina M.A.M.; Crespo, Agricio N. (International Archives of Otorhinolaryngology, 2019)
Introduction The human larynx is a very important organ for communication. Many conditions lead to scarring of the vocal folds, decreasing voice quality.Objective We aimed to determine whether fibroblast growth factors (FGFs) may influence tissue integration of grafted fascia into the vocal folds of an animal model.Methods This is an experimental animal study with 12 adult rabbits that were submitted to a grafting fragment obtained from superficial cervical fascia into the vocal fold lamina propria, bilaterally. The right vocal fold was injected with FGFs. The animals were sacrificed after 1 month or 12 months, depending on the group they were assigned to, and a histological analysis of their vocal folds was performed. We analyzed the histological changes (such as the presence of fibrosis and neovascularization) induced by the acute or chronic inflammatory reactions.Results The FGFs induced acute inflammatory changes in all animals after 1 month of the initial experiment. The presence of FGFs triggered more fibrosis than the expected due to the surgical procedure itself when compared with the control side of all animals after 12 months of the initial experiment.Conclusions Fibroblast growth factors alone do not represent a good therapeutic option in phonosurgery, since we observed higher levels of fibrosis in the vocal fold lamina propria. Further studies combining more substances may be necessary to elucidate the best option to be used in this kind of surgery.
Keywords: vocal folds; rabbits; FGFs; fibroblasts; grafting; fascia